Epidemiological dynamics and molecular characteristics of HIV-1 among transgender women in the Central-West region of Brazil - Diniz e Silva, Bruno Vinícius; Teixeira, Sylvia Lopes Maia; Santos, Paulie Marcelly Ribeiro dos; Magalhães, Larissa Silva; Pilotto, José Henrique; Georg, Ingebourg; Jesus, Carlos Silva de; Silva, Rayana Katylin Mendes Da; Caetano, Karlla Antonieta Amorim; Cook, Robert Lewis; Martins, Regina Maria Bringel; Teles, Sheila Araujo; et al. (Frontiers in Public Health, 2025)
IntroductionThe human immunodeficiency virus (HIV) epidemic disproportionately affects key populations, including transgender women (TGW). Understanding the epidemiological and molecular characteristics on HIV-1 infection among TGW in Brazil, a continental country, is important to support decisions about public health policies. Therefore, this cross-sectional study aimed to evaluate the HIV prevalence and associated risk factors, recency of infection, genetic diversity of HIV-1, transmission clusters, and drug resistance mutations among TGW in Goiás, a state in the Central-West region of Brazil.MethodsA total of 440 participants from three cities in Goiás (Goiânia, Itumbiara, and Jataí) were recruited using Respondent-Driven Sampling. Serum samples were screened for anti-HIV antibodies using rapid tests and an enzyme-linked immunosorbent assay. Recent acquisitions were identified from plasma samples using the Limiting Antigen Avidity assay. Deoxyribonucleic acid was extracted from blood samples, and the partial polymerase gene (protease/reverse transcriptase region) was amplified using a nested polymerase chain reaction. Sequences were subtyped, analyzed for potential transmission networks, and assessed for drug resistance using the Stanford HIVdb program.ResultsMost participants were young, single, self-identified as Black or mixed-race, and had a secondary education level or less. Many reported early sexual debut and multiple high-risk behaviors for sexually transmitted infections. The overall prevalence was 27.3%, with 43.2% classified as recent acquisitions and 56.8% as long-standing. Being over 25 years of age and engaging in chemsex were significantly associated with infection (p < 0.05). Regarding genetic diversity, subtype B was the most prevalent, followed by F1 and C. Ten transmission clusters were identified; each composed of at least two sequences. High prevalence of drug resistance mutations (39.1%) was observed among TGW.ConclusionThese findings underscore the high burden of HIV-1 among TGW in the Central-West region of Brazil and highlight the importance of serological and molecular surveillance in guiding targeted interventions aimed at preventing HIV acquisition and formulating well-informed public health policies for this key population.